Multirepresentation in Physics Learning to Reduce Students’ Misconceptions About Circular Motion Concepts - Rachman, Gazali; Batlolona, John Rafafy (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2025)
Physics education faces significant challenges in addressing students’ misconceptions, particularly regarding the concept of circular motion. This article raises this issue by proposing the application of a multi-representational approach as an effective solution. A descriptive research method was used to analyze the multi-representational abilities of 36 eleventh-grade students, consisting of 12 males and 24 females. The results indicate that before the implementation of this approach, students’ abilities to understand the concept of circular motion were very low, with an average percentage of only 28.70%. However, after the application of multi-representation, this percentage significantly increased to 70.59%. Furthermore, when examining gender aspects more closely, the highest achievements in students’ multi-representational abilities related to the concept of circular motion occurred across all types of representations. This indicates that students are now capable of understanding and communicating physics ideas through various types of representations. These findings suggest that the use of different forms of representation, such as verbal, graphical, image, and mathematical, not only enhances students’ conceptual understanding but also helps them identify and correct existing misconceptions. In conclusion, the integration of a multi-representational approach into the physics curriculum is crucial for improving students’ understanding and reducing conceptual errors. This study recommends ongoing training for teachers in using various representations for instruction, as well as the development of learning modules that include different types of representations to support better student comprehension.